Pandemic-Induced Wealth and Health Inequality and Risk Exposure - Konstantinos Angelopoulos; Spyridon Lazarakis; Rebecca Mancy; Max Schroeder (Center for Economic Studies and ifo Institute (CESifo), 2021)
The main waves of a pandemic and subsequent disease outbreaks in the following years influence the evolution of the distributions of health and wealth, leading to differences in the ability to mitigate future income shocks. We study consumption smoothing and precautionary behaviour associated with the main pandemic waves and recurrent outbreak risk in a model in which health and wealth are jointly determined under income and health risk that are related to disease outbreak risk. We calibrate the model to the UK and find that the impact shock of COVID-19 and recurrent outbreak risk amplify existing inequalities in wealth and health, implying persistent increases in wealth inequality that are characterised by increases in wealth for households in higher income groups and/or with higher initial wealth, and decreases for those in lower income groups and/or with lower wealth. These changes lead to inequality in exposure to post-pandemic income risk and, in particular, an increase in the vulnerability of those already with very little wealth prior to the pandemic. We assess public insurance policy to mitigate income losses for those with low wealth and find that, by disincentivising wealth accumulation and incentivising investment in health for those with low wealth and health, it reduces health inequality and, in the short run, the probability of low consumption, but increases wealth inequality and, in the medium run, the probability of low consumption.
Keywords: E21; D31; I14; D15; E62; 330; pandemics; outbreak risk; wealth inequality; health inequality; risk exposure